(untitled) (Research, Society and Development, 2023)
Objective: To review the literature to elucidate the physiotherapeutic interventions and resources used to monitor trans women undergoing sex reassignment surgery (CRS). Methodology: A literature review was carried out in the databases: MEDLINE/PubMed, BVS, SciELO and PEDro. The descriptors “sex reassignment surgery”, “postoperative care”, “pelvic floor”, “physical therapy” were used, which were adapted according to the database. Studies published in English and Portuguese were included; with full text available; published between 2012 and 2023. Literature review articles, letters to the editor, books, monographs and reviews were excluded. Results: After applying the eligibility criteria, two articles were included in the review. The articles were longitudinal studies, which monitored trans women who underwent CRS and were evaluated and followed up by physiotherapy professionals, before and/or after the surgical procedure. The most used resources were vaginal dilation therapy, kinesiotherapy, biofeedback, desensitization techniques in the surgery area, manual therapy and health education. Conclusion: Transgender women who were monitored by pelvic physiotherapists had fewer post-surgical dysfunctions. However, more robust studies are important to guide the clinical practice of physiotherapists.